2015
DOI: 10.1111/jog.12702
|View full text |Cite
|
Sign up to set email alerts
|

Carbetocin versus intra‐umbilical oxytocin in the management of retained placenta: A randomized clinical study

Abstract: Aim: This study aimed to compare the hemodynamic profile and efficacy of carbetocin versus intra-umbilical oxytocin in the management of retained placenta following vaginal delivery. Material and Methods: In this randomized clinical study, women with retained placenta for more than 30 min were assigned to receive either an i.v. bolus of 100-μg carbetocin (n = 38) or an intra-umbilical vein injection of 50 IU oxytocin in 30 mL saline (n = 40). The main parameters evaluated were the success rate for expulsion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(61 reference statements)
0
6
1
Order By: Relevance
“…18 Carbetocin can shorten the third stage, prevent and treat retained placenta at term, and prevent and treat second trimester abortion. 19 However, our results were inconsistent with the findings of a previous study, in which the additional effects of carbetocin were presumed to be trivial because of thinning in the lower uterine myometrium, thereby reducing the immunoreactivity of oxytocin receptors relative to the upper part of the uterus. 20 We noted that the significant differences in outcomes between treatments were mainly due to the contributions of the emergency Caesarean section group.…”
Section: Discussioncontrasting
confidence: 99%
“…18 Carbetocin can shorten the third stage, prevent and treat retained placenta at term, and prevent and treat second trimester abortion. 19 However, our results were inconsistent with the findings of a previous study, in which the additional effects of carbetocin were presumed to be trivial because of thinning in the lower uterine myometrium, thereby reducing the immunoreactivity of oxytocin receptors relative to the upper part of the uterus. 20 We noted that the significant differences in outcomes between treatments were mainly due to the contributions of the emergency Caesarean section group.…”
Section: Discussioncontrasting
confidence: 99%
“…[1,9,16,17] In this meta-analysis, we included nine trials to compare IUV injection route with conventional IM and IV routes for administration of oxytocic agents. Of which, four trials compared IUV versus IV oxytocin, [6,[12][13][14] two trials compared IUV oxytocin with © 2019 IJNR | Published by Innovational Publishers IV carbetocin, [5,11] and three trials compared IUV versus IM oxytocin. [4,7,15] The trials comparing IUV oxytocin with IV oxytocin found compelling evidence that IUV oxytocin is associated with a statistically significant reduction in duration of the third stage of labor, reduction in amount of blood loss in the third stage of labor, and low placental separation time.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were hospital-based and conducted in labor room and labor operation theater. The studies included pregnant women undergoing normal vaginal delivery or cesarean delivery and with a sample size ranging from 78 [11] to 400. [4] Among the articles included in the analysis, four studies compared IUV oxytocin with IV oxytocin, [6,[12][13][14] which favored IUV oxytocin administration for comparatively short length of the third stage of labor, less amount of blood loss, and less time needed for placental expulsion.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations